Hydrophobic halochromic aerogel capable of reversibly measuring acidic and basic vapors - Jeong Hui Lee (AIP Publishing LLC, 2021)
A halochromic sensor that can visually and quickly monitor the information regarding the exposure of harmful chemicals to the human body is highly valuable in the safety and industrial fields. A general halochromic sensor uses a hydrophilic matrix to increase its detection sensitivity by promoting the diffusion of foreign materials. However, it is difficult to maintain the reversibility, durability, and stability of the color change in the halochromic sensor due to the loss of halochromic dyes under continuous exposure to chemicals. This study investigates a hydrophobic halochromic aerogel sensor that is stable even when exposed to various external environments and reacts to both acids and bases. By embedding halochromic dyes in silica aerogels with a porous structure and hydrophobicity, the leaching of halochromic dyes can be prevented even when the aerogels are placed in aqueous solutions. Hydrophobic halochromic aerogels can detect vapors generated in acidic and basic solutions, and the color change in hydrophobic halochromic aerogels reacts stably even with repeated acid and base environmental changes, enabling accurate acid or base concentration detection. In addition, halochromic aerogels can be easily applied to various platforms because they can be combined with fabric, concrete blocks, pipes, and polymers such as polydimethylsiloxane to create composites. The halochromic aerogels derived in this study are expected to contribute to the development of color change sensors applicable to various work environments by greatly improving the color change reversibility, durability, and stability that are the most important characteristics of robust halochromic sensors.